Conflict or Harmony: Framing of Wildlife News in a Biodiversity Hotspot - Simplicious J. Gessa; William Tayeebwa; Vincent Muwanika; Jessica M. Rothman (Journalism and Media, 2023)
Newspapers are avenues of the media that can influence public perceptions. Newspapers are especially important to engender support for wildlife protection because they reach populations who do not necessarily encounter wildlife frequently. Our research examined how newspaper media depict wildlife-related information in Uganda, a country which hosts high biodiversity. A content analysis was performed in two widely read daily newspapers, namely, the New Vision (n = 258) and Daily Monitor (n = 267), for news articles published in selected years between 2010 and 2019. The findings show a balance between positive and negative articles published in this period. New Vision had 51.5% of its articles on wildlife negatively framed while Daily Monitor had 50% of its articles positively framed. The articles that focused on the positive benefits from wildlife were the longest with 803 ± 525 words. One of the themes that featured prominently was the impact of developments on wildlife such as successful conservation practices, management interventions to save wildlife, and NGO conservation support to wildlife protection and population growth. Overall, newspaper articles addressed efforts that called for wildlife survival, but conflict still featured prominently. Measures to sensitize journalists, such as media engagement, wildlife tours, and integration with scientists, are needed to better implement conservation media. We also suggest that the media focus on the intrinsic benefits of biodiversity conservation, and that scientists be better integrated into wildlife news stories.